The Relationship Between Taste, Price, and Packaging Design To Consumer Purchase Interest in Ketakasi Coffee in Si-domulyo Village, Silo District, Jember Regency - Efendi, Muhammad Choirul; Prayuginingsih, Henik; Fauzi, Nurul Fathiyah (International Applied Science, 2024)
Companies always research buyer behavior to determine consumer desire for their products. This increases consumer satisfaction so that the product is liked and company profits also increase. Nowadays, coffee can be processed into various flavors that can be enjoyed. This phenomenon gave rise to the idea for farmer groups or cooperatives in Sidomulyo Village, Silo District, Jember Regency to produce coffee with the distinctive taste of Ketakasi coffee packaged in various designs. The research objectives are (1) Identifying consumer perceptions of the taste of Ketakasi coffee (2) Identifying consumer perceptions of the price of Ketakasi coffee (3) Identifying consumer perceptions of Ketakasi coffee packaging design (4) Analyzing the relationship between taste, price and packaging design with purchase intention Ketakasi coffee consumers. The research method uses a qualitative descriptive method which was carried out purposively on consumers of Kertakasi robusta coffee. The research sample consisted of 33 consumers based on Taro Yamane's formula calculations. The research results show (1) Ketakasi robusta coffee has a strong aroma, strong aftertaste, and delicious taste (2) The price of canned Ketakasi coffee is affordable, the price is in line with product quality and competitive with similar products (3) Robusta coffee packaging design. Kertalasi displays attractive packaging and clear product information (4) The relationship between taste, price, and packaging design on consumers' buying interest in Ketakasi coffee in Sidomulyo Village, Silo District, Jember Regency is that taste has a sufficient but not significant correlation, price has a sufficient correlation and significant, and packaging design has a very weak but not significant correlation.